USING PROGRESSIVE PEDAGOGIES TO ENHANCE LEARNER AUTONOMY - Lindsay Miller (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
In this presentation I firstly review different approaches and methods that have been used to teaching English. Based on these approaches and methods, our understanding of how students learn their second language has been greatly enhanced. However, students in the 21st Century have more demands and needs than previously and we now have to use more progressive pedagogies to teach them. Some features of a progressive pedagogical approach are: learners are active participants; teachers are facilitators and guides; there is shared decision-making by the group; learning is seen as part of real-life experiences; and learning is conceptualized as a spiral where knowledge is constructed through experience and social interaction (Peters, 2012). This type of pedagogical approach is student-centred and lends itself to the promotion of learner autonomy. By way of an example I will talk about a university level English for Science course I have been involved in developing and teaching over the past five years. Keywords: Progressive pedagogies, learner autonomy, project learning.